Hubungan antara Kecerdasan Emosional dan Adaptabilitas Karier Siswa Sekolah Menengah Kejuruan (SMK) “X” di Kota Salatiga - Zania Timur Maulidina; Doddy Hendro Wibowo (Humanitas (Jurnal Psikologi), 2021)
Students need to prepare themselves for their desired career. This study aims to determine the relationship between emotional intelligence and career adaptability among vocational students. This study used a sample of 66 students of SMK "X" class XII with a non-probability sampling technique. The instrument used in this study was translated from the Career Adapt-Abilities Scale (CAAS) and Wong and Law Emotional Intelligence Scale (WLEIS). The results of data analysis using the Pearson Product Moment correlation technique showed the coefficient value of r = 0.945 (p <0.05), meaning that there was a significant positive relationship between emotional intelligence and career adaptability students of SMK "X" in Salatiga. The research implication for vocational high school students is the importance role of emotional intelligence through process of recognizing the emotions of oneself and others so as to increase career adaptability to face the career world. Keywords: emotional intelligence, career adaptability of vocational students